2023
DOI: 10.1097/js9.0000000000000683
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness and prognostic model of hepatic arterial infusion chemotherapy for hepatocellular carcinoma with high tumor burden and/or Vp4 tumor thrombus compared with sorafenib: a post-hoc analysis of the FOHAIC-1 trial

Qi-Feng Chen,
Ning Lyu,
Xun Wang
et al.

Abstract: Objectives: The phase III FOHAIC-1 trial revealed that hepatic arterial infusion of chemotherapy (HAIC) improved overall survival compared to sorafenib in the high-risk hepatocellular carcinoma (HCC). This study therefore set out to evaluate the cost-effectiveness and establish a prognostic clinico-radiological score of HAIC. Materials and methods: A total of 409 patients with high-risk HCC who received HAIC between 2014 and 2020 were included. A Markov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…To assess cost-effectiveness, we calculated the incremental cost-effectiveness ratio (ICER), which reflects the additional cost per 1 quality-adjusted life years (QALY). In our primary analysis, a willingness-to-pay (WTP) threshold of $30,492/ QALY was applied using 3 times the GDP per capita [16]. A discount rate of 3% per annum was applied to adjust for inflation, consistent with the pharmacoeconomics guidelines [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess cost-effectiveness, we calculated the incremental cost-effectiveness ratio (ICER), which reflects the additional cost per 1 quality-adjusted life years (QALY). In our primary analysis, a willingness-to-pay (WTP) threshold of $30,492/ QALY was applied using 3 times the GDP per capita [16]. A discount rate of 3% per annum was applied to adjust for inflation, consistent with the pharmacoeconomics guidelines [13].…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies, based on the IMbrave150 trial, concluded that atezolizumab plus bevacizumab was not a cost-effective first-line option compared with sorafenib in patients with unresectable HCC [19,20]. Previously, Chen et al found HAIC-FO was a cost-effective strategy for patients with high-risk factors (the ICER of HAIC-FO was $10190.41/QALYs, compared with sorafenib) [16]. Consistently, our study showed the costeffectiveness of HAIC-FO vs that of sorafenib in advanced HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation